2021
DOI: 10.1186/s12935-020-01742-6
|View full text |Cite
|
Sign up to set email alerts
|

Automatic model for cervical cancer screening based on convolutional neural network: a retrospective, multicohort, multicenter study

Abstract: Background The incidence rates of cervical cancer in developing countries have been steeply increasing while the medical resources for prevention, detection, and treatment are still quite limited. Computer-based deep learning methods can achieve high-accuracy fast cancer screening. Such methods can lead to early diagnosis, effective treatment, and hopefully successful prevention of cervical cancer. In this work, we seek to construct a robust deep convolutional neural network (DCNN) model that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…The most important findings of our study are as follows: (1). There are currently few network architectures designed specifically for cervical cancer cell detection in Pap smear images [42,[44][45][46]. Based on one of the currently top-performing detectors faster RCCN-FPN [57]…”
Section: The Main Findings Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The most important findings of our study are as follows: (1). There are currently few network architectures designed specifically for cervical cancer cell detection in Pap smear images [42,[44][45][46]. Based on one of the currently top-performing detectors faster RCCN-FPN [57]…”
Section: The Main Findings Of the Studymentioning
confidence: 99%
“…As discussed above, Images with higher magnification are strongly favorable for the detection of cervical cancerous cells. A recent study [44] based on the Faster RCNN model used TCT images of 400x and achieved AUC=0.67 with IOU threshold=0.5. which is about 12% patches appear too small, the detector's performance may degrade to a point that the cells are miss-classified or missed entirely.…”
Section: Image Magnification and Iou Thresholdmentioning
confidence: 99%
See 1 more Smart Citation
“…The object detection methods have also begun to find applications for cervical cancer detection in cervical cytology images. At present, there are few network architectures designed specifically for the specific task of cervical cancer detection [ 41 , 42 , 43 , 44 , 45 , 46 ]. Xu et al [ 45 ] used the generic Faster RCNN for the detection of abnormal cells in cervical smear images scanned at 20× and showed that detection of various abnormal cells was feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the precise positions of the cell nuclei are less important because the cells tend to form clumps in the Pap smear slides. Tan et al [ 44 ] also used Faster RCNN architecture for cervical cancer cell detection in ThinPrep cytologic test (TCT) images scanned with a seamless slider at up to 400× and achieved AUC of 0.67. More recently, Ma et al [ 42 ] proposed an improved Faster RCNN-FPN architecture for cervical cancer detection in cropped patches out of positive Pap smear images.…”
Section: Introductionmentioning
confidence: 99%